The effect of two different variety of sesame seed color on the sesame paste tahini - Zuher Karem, Sheraz; Darwin Hawar Mohammed (University of Thi-Qar Journal of agricultural research, 2025)
This research assessed the sensory attributes of tahini made from two types of sesame seeds—brown and white—sourced from the Aya local market in Erbil, Iraq. After being cleaned by hand, the seeds were dry-roasted to bring out their flavour and then crushed into a paste in a high-speed food processor. The tahini was put in sealed jars for examination, and a pinch of salt was added to each batch. A panel of 25 people who were acquainted with sesame goods did a sensory assessment using a 9-point hedonic scale to rate the items' look, smell, feel, taste, aftertaste, and overall acceptability. Statistical study (ANOVA, p < 0.05) demonstrated substantial disparities between the two types. White sesame tahini always got better scores in all categories, with the biggest differences in appearance (8.1 ± 0.6 vs. 7.2 ± 0.8), scent (8.3 ± 0.5 vs. 7.5 ± 0.7), and texture (8.0 ± 0.7 vs. 6.8 ± 0.9). The findings show that tahini made from white sesame seeds has a more attractive colour, smoother texture, and milder flavour, making it more generally acceptable (8.3 ± 0.5) than brown sesame tahini (6.9 ± 0.9). These results provide both customers and producers useful information about which kind of sesame seeds to use to make high-quality tahini.